(untitled) (Research, Society and Development, 2020)
Heat stroke is part of solar energy that spreads without the need for a material medium and is represented by the hours of the day that the solar disk remains visible on the earth’s surface. The objective is to characterize the climatic conditions of insolation using the interpolation method for the area of the hydrographic basin of the Ipojuca River and its surroundings, elaborating a monthly and annual graph for the period from 1962 to 2019. The average climatological data of the total monthly and annual sunshine were generated by the simple interpolation method, using electronic spreadsheets to extract the averages values ​​of the monthly, annual, median, standard deviation, coefficient of variance, maximum and minimum absolute values. Total sunstroke is greater than the cloud coverage in the period from August to March, totaling 1861.8 hours and tenths, while in the same period, the cloud coverage is 0.45 tenths. Low cloud cover, temperature fluctuations and low or no ground cover conditions these incidences of insolation rates above normal. The importance of heat stroke is verified for purposes of applicability in the agricultural sectors, energy generations, aiming at helping industrial parks, energy distributors, agricultural sector and climatic studies that are scarce or widespread. It is observed that the deviations are positive, showing increases in the monthly and annual values, even though the straight line trends show us insignificant reductions for the period studied. The trend lines of the respective 12 months are negative and without insignificance, agreeing with the calculations of the moving averages, stating that there has been a reduction in the sunstroke in the next 9 years and, after 10 years, the insolation rates return to the level of the historical average.